2005
DOI: 10.1901/jaba.2005.139-04
|View full text |Cite
|
Sign up to set email alerts
|

An Example of Discovery Research Involving the Transfer of Stimulus Control

Abstract: The initial purpose of the present study was to replicate procedures for teaching preschool children to recruit attention at appropriate times by having an experimenter signal the availability and unavailability of attention (i.e., arrange a multiple schedule involving reinforcement and extinction; Tiger & Hanley, 2004). Following the development of discriminated social responding, the schedule-correlated stimuli were removed (i.e., a mixed schedule of reinforcement was arranged). However, discriminated respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…Components were randomly alternated to minimize the potential that a temporal discrimination would develop (something that would be highly unlikely under typical classroom conditions). Further, individual components were brief to minimize the likelihood of the participant discriminating the operating contingencies independent of schedule-correlated stimuli (e.g., Tiger & Hanley, 2005). The order of these components was randomly determined prior to each session block, but was held constant across each session within a session block (i.e., the pattern of reinforcement and extinction components was identical across exposure to the three terminal links).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Components were randomly alternated to minimize the potential that a temporal discrimination would develop (something that would be highly unlikely under typical classroom conditions). Further, individual components were brief to minimize the likelihood of the participant discriminating the operating contingencies independent of schedule-correlated stimuli (e.g., Tiger & Hanley, 2005). The order of these components was randomly determined prior to each session block, but was held constant across each session within a session block (i.e., the pattern of reinforcement and extinction components was identical across exposure to the three terminal links).…”
Section: Methodsmentioning
confidence: 99%
“…We determined the integrity of implementation of the independent variable by analyzing the correspondence between the number of social approaches emitted and the number of instances of attention delivery within reinforcement and extinction components of the multiple-schedule (S+/S2, S+) and mixed-schedule arrangements (Tiger & Hanley, 2005). During reinforcement components, the smaller of the two numbers were divided by the larger number.…”
Section: Treatment Integritymentioning
confidence: 99%
“…Schedule thinning is therefore often conducted following the initial demonstration of treatment effects. Although methods of schedule thinning have included the restriction of access to communication materials (e.g., Roane, Fisher, Sgro, Falcomata, & Pabico, 2004), delay-to-reinforcement (e.g., Hagopian et al, 1998), and fixed-interval schedules (e.g., Hanley, Iwata, Thompson, 2001), multiple schedules have received increasing attention as a way to thin schedules (e.g., Fisher et al, 1998;Hanley et al, 2001;Tiger & Hanley, 2004;Tiger & Hanley, 2005;Tiger, Hanley, & Heal, 2006;Sidener, Shabani, Carr, & Roland, 2006). Ferster and Skinner (1957) defined a multiple schedule as ''two or more alternating schedules of reinforcement with a different stimulus present during each' ' (p. 503).…”
Section: Introductionmentioning
confidence: 99%
“…Ferster and Skinner (1957) defined a multiple schedule as ''two or more alternating schedules of reinforcement with a different stimulus present during each' ' (p. 503). Several studies have effectively thinned FCT schedules by signaling both periods of reinforcement and extinction (e.g., Hanley et al, 2001;Tiger & Hanley, 2004;Tiger & Hanley, 2005;Sidener et al, 2006). For example, Hanley et al (2001) observed that multiple schedules, in which both reinforcement and extinction periods were associated with different stimuli, more effectively controlled collateral problem behavior than mixed schedules, in which neither period was signaled.…”
Section: Introductionmentioning
confidence: 99%
“…That is, in addition to arranging periods in which reinforcement for a target behavior is available and unavailable (i.e., EXT), researchers have associated these periods with a variety of salient environmental stimuli to promote stimulus control. In particular, multiple schedules have been used (a) to promote stimulus control over high-rate appropriate behaviors (e.g., frequent requests for adult attention) in typically developing children (Cammilleri, Tiger, & Hanley, 2008; Tiger & Hanley, 2004, 2005; Vargo, Heal, Epperley, & Kooistra, 2014), (b) to teach individuals with intellectual disabilities who engage in severe problem behavior to request the putative reinforcer maintaining problem behavior only when the S D is present and to gradually tolerate longer periods in which the S D is absent (Betz, Fisher, Roane, Mintz, & Owen, 2013; Fisher, Kuhn, & Thompson, 1998; Hagopian, Toole, Long, Bowman, & Lieving, 2004; Hagopian, Contrucci Kuhn, Long, & Rush, 2005; Hanley, Iwata, & Thompson, 2001; Rooker, Jessel, Kurtz, & Hagopian, 2013), and (c) to signal periods of punishment in the treatment of severe problem behavior maintained by automatic reinforcement displayed by individuals with intellectual disabilities (Anderson, Doughty, Doughty, Williams, & Saunders, 2010; Doughty, Anderson, Doughty, Williams, & Saunders, 2007; Rollings & Baumeister, 1981). …”
mentioning
confidence: 99%